GOVERNMENTAL SOCIAL-CHRISTIANITY: AN ADMINISTRATIVE VIEW TO HISTORY - Bolaños Garita, Rolando (2020)
This contribution was made within the framework of our academic-research work at UNED, always in search for a better understanding of the national reality. For this reason, and from a qualitative-documentary perspective, the moments were approached when, apparently, social-christian ideology –Social Doctrine of Catholic Church– influenced internal economic conditions, given its proximity to the current of economic liberalism. In this way, the articles deems the start in the 1940s and until 2006, which allows to infer the existence of a political group with catholic tendencies, but that at no time hid their preference for such a current that has not taken the radical form that they advocate.